Determining the role and relative importance of predator avoidance and nutrition as processes influencing herbivore utilisation of burnt areas in Satara, Kruger National Park, South Africa - Luhdo, Zoe (My University, 2016)
This study aimed to determine the role and relative importance of predator avoidance and nutrition as processes influencing herbivore utilisation of burnt areas, at Satara, Kruger National Park by using variation in fire size and fire season. The driving factors investigated included forage quality, forage quantity, vegetation structure and predation risk. The effect of fire size and season on the landscape was tested by recording grass height, greenness, grass nutrient sampling and visibility. Results showed that fire size and season had a significant impact on the physical environment by decreasing grass/forage quantity post-fire but increasing grass/forage quality. Over time the plots returned to near pre-fire conditions, with forage quantity increasing (grass height and biomass) and forage quality decreasing (nitrogen availability). Visibility increased immediately post-fire, more significantly in regards to herbivores with their heads in a “head-down/grazing” position than in a “head raised/vigilant” position. As with forage quantity and quality, visibility returned to near pre-fire conditions at the end of the study sampling period. The response of animals to these changes in the environment was recorded through dung counts, camera traps and behavioural observations. I found that there was increased use of burnt plots post-fire through comparing herbivore presence on plots burned in different sizes and seasons, day/night utilisation of plots, and using behaviour data I could determine to what extent forage and predation risk were driving the use of burnt areas. I focused on three herbivore species (Aepyceros melampus, Connochaetes taurinus and Equus quagga) which varied in terms of body size digestive systems, forage type, and social behaviour. As expected, I found that predation risk did appear to be more important in driving the behaviour of the smaller-bodied herbivores but both nutrient requirements and susceptibility to predation were shown to play a role in explaining the use of burnt areas for all three herbivore species. Variation between plots in environmental factors such as tree density, forb percentage and distance to water, were found to be not significant and thus did not confound our results
A Dissertation submitted to the Faculty of Science in fulfilment of the requirements for the degree: Master of Science In School of Animal, Plants and Environmental Sciences, University of Witwatersrand Johannesburg 2015
Keywords: Kruger National Park (South Africa); Landscape assessment.; Predation (Biology); Herbivores -- South Africa -- Kruger National Park.